Decreased VEGFR2 expression and increased phosphorylated Akt1 in the prefrontal cortex of individuals with schizophrenia. (November 2016) - Hino, Mizuki; Kunii, Yasuto; Matsumoto, Junya; Wada, Akira; Nagaoka, Atsuko; Niwa, Shin-ichi; Takahashi, Hitoshi; Kakita, Akiyoshi; Akatsu, Hiroyasu; Hashizume, Yoshio; Yamamoto, Sakon; Yabe, Hirooki
Abstract: The Akt signaling pathway involves various cellular processes and depends on extracellular stimuli. Since Akt signaling participates in cytoprotection, synapse plasticity, axon extension, and neurotransmission in the nervous system, alteration in Akt signaling might be a potential cause of schizophrenia. In this study, we performed multiplex fluorescent bead based immunoassays for members of the Akt signaling pathway in postmortem brains of controls and patients with schizophrenia. Vascular endothelial growth factor receptor 2 (VEGFR2/KDR) was significantly decreased in the prefrontal cortex (PFC) of patients with schizophrenia, and the expression level of VEGFR2 was inversely correlated with the positive symptom subscale of the Diagnostic Instrument for Brain Studies (DIBS) in patients with schizophrenia. There was also an increase in phosphorylated Akt1 in the PFC in the patients, though the ratio of phospho/total Akt1 is not significantly different. In the nucleus accumbens (NAcc) there was no significant difference in expression and phosphorylation levels of Akt signaling proteins. Genetic analysis revealed a significant correlation of a SNP of KDR (rs7692791) with ERK1/2 and Akt1 phospho/total rates. Since VEGFR2 participates in angiogenesis and neurotrophic activation, either or both functions might be responsible for onset of schizophrenia.